2021
DOI: 10.1111/and.14027
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA damage and seminal antioxidant activity in subfertile men

Abstract: Supraphysiological ROS levels can lead to apoptosis, lipid peroxidation, and DNA and protein damage. This pilot study aimed to investigate the sperm oxidative damage in subfertile men, to describe the relationship between the antioxidant system and ROS. Sixty‐four semen samples were categorised according to the evaluated routine parameters (WHO, WHO laboratory manual for the examination and processing of human semen, 2010). Results were cross‐referenced with the DNA damage [Comet (n = 53) and TUNEL (n = 49) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…To our knowledge, our study is the first to explore the associations between HAA exposure and human spermatozoa apoptosis and DNA damage, expanding our previous findings showing that urinary TCAA concentrations were inversely associated with traditional sperm quality parameters (e.g., sperm count, concentration, motility, and morphology) among men recruited from the same reproductive center in 2008 and 2011–2012 . Previous studies have shown that spermatozoa apoptosis and DNA damage parameters are highly reproducible and have the strength of providing additional aspects of male reproductive health and fertility. In support of this notion, we found a slightly stronger inverse association between urinary TCAA concentrations and the percentage of dead spermatozoa among men with normal semen quality. Interestingly, the median urinary concentration of TCAA in our present study population (2.38 μg/L) was lower than that of men recruited from the same reproductive center in 2008 (7.40 μg/L) and 2011–2012 (7.97 μg/L).…”
Section: Discussionsupporting
confidence: 80%
“…To our knowledge, our study is the first to explore the associations between HAA exposure and human spermatozoa apoptosis and DNA damage, expanding our previous findings showing that urinary TCAA concentrations were inversely associated with traditional sperm quality parameters (e.g., sperm count, concentration, motility, and morphology) among men recruited from the same reproductive center in 2008 and 2011–2012 . Previous studies have shown that spermatozoa apoptosis and DNA damage parameters are highly reproducible and have the strength of providing additional aspects of male reproductive health and fertility. In support of this notion, we found a slightly stronger inverse association between urinary TCAA concentrations and the percentage of dead spermatozoa among men with normal semen quality. Interestingly, the median urinary concentration of TCAA in our present study population (2.38 μg/L) was lower than that of men recruited from the same reproductive center in 2008 (7.40 μg/L) and 2011–2012 (7.97 μg/L).…”
Section: Discussionsupporting
confidence: 80%
“…Supplementation therapy has been widely employed in the context of infertility as a mean to improve the success rate in achieving pregnancy both spontaneously and by means of ART. In this context, the evidence strongly suggests that oxidative stress plays a central role in idiopathic infertility [ 15 , 16 , 17 ], thus raising interest towards antioxidant therapy in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, which is known to play a pathogenic role in a variety of diseases [ 10 , 11 ], may also have a relevant impact on spermatozoa’s activity. Hence, lifestyle factors such as smoking, alcohol use, obesity, varicocele, infections and psychological stress, which have been associated with infertility and poor sperm quality [ 12 , 13 , 14 ] may indeed exploit their effect through oxidative stress [ 15 , 16 , 17 ]. The process is thought to influence between 30 and 80% of subfertility cases, and, for this reason, the category of MOSI (male oxidative stress infertility) was created [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to regulatory and ethical concerns, it is difficult to directly detect the oxidative stress state of human oocytes and embryos to reveal the effects of sperm ROS on embryo development. There are a limited number of studies on the effects of sperm ROS on in vitro embryos, and most of these studies did not differentiate female infertility factors [6][7][8], ignoring the importance of oocyte quality in embryo development and the large differences in oocyte quality in women with infertility of different etiologies [9].…”
Section: Introductionmentioning
confidence: 99%